Magnetodynamo lifetimes for rocky, Earth‐mass exoplanets with contrasting mantle convection regimes. Issue 5 (16th May 2013) - van Summeren, Joost; Gaidos, Eric; Conrad, Clinton P.
Abstract : [1] We used a thermal model of an iron core to calculate magnetodynamo evolution in Earth‐mass rocky planets to determine the sensitivity of dynamo lifetime and intensity to planets with different mantle tectonic regimes, surface temperatures, and core properties. The heat flow at the core‐mantle boundary (CMB) is derived from numerical models of mantle convection with a viscous/pseudoplastic rheology that captures the phenomenology of plate‐like tectonics. Our thermal evolution models predict a long‐lived (~8 Gyr) field for Earth and similar dynamo evolution for Earth‐mass exoplanets with plate tectonics. Both elevated surface temperature and pressure‐dependent mantle viscosity reduce the CMB heat flow but produce only slightly longer‐lived dynamos (~8–9.5 Gyr). Single‐plate ("stagnant lid") planets with relatively low CMB heat flow produce long‐lived (~10.5 Gyr) dynamos. These weaker dynamos can cease for several billions of years and subsequently reactivate due to the additional entropy production associated with inner core growth, a possible explanation for the absence of a magnetic field on present‐day Venus. We also show that dynamo operation is sensitive to the initial temperature, size, and solidus of a planet's core. These dependencies would severely challenge any attempt to distinguish exoplanets with plate tectonics and stagnant lids based on the presence or absence of a magnetic field. Key Points: Long‐lived (~8‐10.5 Gyr) dynamos are calculated for rocky Earth‐mass exoplanets Characterization of exoplanets requires well‐determined core properties Venus may lack a magnetic field due to a CMB heat flow lower than Earth's